Inclusão escolar com apoio: uma análise do serviço do ensino itinerante - Moreira, Maria Helena Bimbatti [UNESP]; Dall'Acqua, Maria Júlia Canazza [UNESP] (My University, 2010)
We investigated the process of inclusion in the school common areas, tracking the performance of a traveling school teacher (teaching support service specialist), type of service in Special Education, as a support to the school's educational proposal. Objectives: To identify, describe and analyze the performance of itinerant school teacher in a school of mainstream school, with students and their teachers, to analyze the perception of two teachers of the common teaching about the process of integration of pupils with special educational needs in their classes; examine the roles and responsibilities of itinerant school teacher through an exploratory qualitative approach. Participants: an itinerant school teacher, two teachers and two of the common teaching students with special educational needs included in mainstream school. Observations were made weekly at the school over a period of six months, semi-structured interviews with teachers and document analysis. The results showed different facets of roaming at the intersection with the common teaching among them may be noted that acts as a parallel system in the common school, creating a gap between them which may compromise or disadvantage of the dynamic performance of service support, but this gap is overcome at critical times facing the mainstream school, where this service benefit the child's learning process and promotes their inclusive education policy.

Investigou-se o processo de inclusão nos espaços da escola comum, acompanhando a atuação de uma professora do ensino itinerante (serviço de apoio pedagógico especializado), modalidade de serviço em Educação Especial, como ponto de apoio à proposta pedagógica da escola. Objetivos: identificar, descrever e analisar a atuação da professora do ensino itinerante em uma escola do ensino comum, com alunos inseridos e seus professores, analisar a percepção de duas professoras do ensino comum sobre o processo de inserção de alunos com necessidades educacionais especiais em suas classes; averiguar as atribuições e responsabilidades da professora do ensino itinerante por meio de um estudo exploratório com abordagem qualitativa. Participantes: uma professora do ensino itinerante, duas professoras do ensino comum e dois alunos com necessidades educacionais especiais inseridos no ensino comum. Foram realizadas observações semanais na escola num período de seis meses, entrevistas semi-estruturadas com as professoras e análise documental. Os resultados mostraram diferentes facetas do serviço itinerante na intersecção com o ensino comum, entre elas pode se destacar que atua como um sistema paralelo na escola comum, gerando um hiato entre ambos o que pode comprometer ou desfavorecer a dinâmica de realização do serviço de apoio, mas esta “lacuna” é superada nos momentos críticos enfrentados pelo ensino comum, nos quais este serviço beneficia a aprendizagem da criança e favorece seu processo inclusivo no ensino comum.
Inclusion in school with support: a review of the service of education itinerant Brazilian
Keywords: Inclusive education; Education itinerant; Teaching support; Educação Inclusiva; ensino itinerante; apoio pedagógico